Cleavage pattern and development of isolated D blastomeres in bivalves. Issue 1 (24th July 2014) - Hashimoto, Naoki; Kurita, Yoshihisa; Murakami, Kana; Wada, Hiroshi
ABSTRACT Although bivalves develop through spiral cleavage patterns, similar to other lophotrochozoans, the cleavage pattern of D lineage blastomeres is unique, since 2d shows four rounds of stereotypic unequal cleavage before bilateral cleavage of the largest derivative of 2d: 2d1121. This unique modification of spiral cleavage is directly associated with the characteristic morphology of bivalves, namely, bilaterally separated shell plates, because the bilateral shell plates are thought to be derived from the bilateral derivatives of 2d1121. In this report, to determine whether the unique cleavage pattern of bivalves is regulated depending on the interaction with other cells or by cell autonomous mechanisms, we performed cell isolation experiments and observed subsequent cleavage patterns of isolated blastomeres. When focusing on the largest derivatives of D blastomeres, 8% of isolated D blastomeres followed the cleavage pattern of normal development up to bilateral cleavage. Importantly, the remainder of the partial embryos ended cleavage before that stage, and none of the isolated blastomeres showed abnormal cleavage patterns. We also examined the development of isolated blastomeres and found that isolated D blastomeres could develop shell plates, whereas larvae developed from AB blastomeres never had shell plates. Based on these observations, we concluded that D blastomeres control their unique cleavage pattern through intrinsic mechanisms and develop shell glands autonomously without any cell–cell interaction with other lineages. J. Exp. Zool. (Mol. Dev. Evol.) 324B: 13–21, 2015. © 2014 Wiley Periodicals, Inc.